2002
DOI: 10.1121/1.4778622
|View full text |Cite
|
Sign up to set email alerts
|

Harmonics to noise ratio in vocal professional voices

Abstract: There is no arguing about the importance of voice, especially in groups of vocal professional voices. The question is what characterizes, the most, normal or pathological voice in relation to aspects of human working life. Harmonics to noise ratio, according to findings from the field of voice disorders, is the most representative method to differ normal from pathological voice. In this research significant differences were found in harmonics to noise ratio in relation to the length of the working age of 29 te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…23 In one study, it was found that more professional teachers had lower level of HNR value. 24 We found significant reduction of maximum phonation time (MPT) at the end of workday {before teaching 23.…”
Section: Discussionmentioning
confidence: 81%
“…23 In one study, it was found that more professional teachers had lower level of HNR value. 24 We found significant reduction of maximum phonation time (MPT) at the end of workday {before teaching 23.…”
Section: Discussionmentioning
confidence: 81%